Climate change, 'slow violence' and the indefinite deferral of responsibility for 'loss and damage' - Dehm, Julia (Griffith law review, 2020)
This article traces debates within international climate regime on loss and damage from climate impacts. Impacts from climate change should be understood as incremental violence structurally over-determined by international relations of power and control that affect most acutely those who contributed least to dangerous levels of anthropocentric greenhouse gas emissions. Calls for compensation or reparation for ‘loss and damage’ are therefore a demand for climate justice. This article shows how questions of loss and damage were initially avoided within the climate regime. At the nineteenth Conference of the Parties in December 2013, the 'United Nations Framework Convention on Climate Change' (UNFCCC) adopted the Warsaw International Mechanisms for Loss and Damage (WIM) associated with climate change. However, even then questions of compensative or reparative justice were persistently evaded. The institutionalisation of the WIM focused on questions of comprehensive risk assessment and disaster risk reduction and the promotion of privatised, insurance-based and financialised approaches to financing loss and damage. These operate in different ways to displace responsibility away from historical polluters, by nationalising responsibility to anticipate and prepare for disasters and seeking to responsibilise the vulnerable and risk-exposed subject.